THE IMPLEMENTATION OF COOPERATIVE LEARNING METHOD IN READING COMPREHENSION SUBJECT FOR THE SECOND YEAR-STUDENTS OF SMAN 9 MAKASSAR - Andi Mushrihah (Jurnal Ilmiah Pena: Sains dan Ilmu Pendidikan, 2019)
This study aimed to examine The Implementation of Cooperative Learning Method in Reading Subject for The Second Year-Students of SMAN 9 Makassar. There are three problems of this study, such as (1) How the Cooperative Learning Method influenced the Second Year-Students achievements in SMA Negeri 9 Makassar,  (2) The Students Interest in Reading Comprehension Subject which the Cooperative Learning Method Applied For, and (3)  What extent the Cooperative Learning Method improves the Reading Comprehension in terms of Literal, inferential, and Critical Comprehension. Moreover, the implementation of Cooperative Learning Method concerned to analyze the student’s abilities by applying this method in Reading Comprehension Subject regarding to its techniques and kinds of reading. The result of this study showed that the percentage students’ mastery for pre-test and post-test in understanding of Reading Subject. From the analysis conducted, there are 2 (two) students are in a VERY GOOD category, whereas 26 Students in a GOOD Percentage and 2 Students placed in FAIR category for the Pre-Test Achievement. The Post-Test Percentage after Learning Method applied, the experimental class achievement’s students have significantly increased where 4 students are in EXCELLENT grade, while 19 students have VERY GOOD category, and about 7 Students placed in a GOOD category. However, the questionnaire given to the students covered the statements about the students’ interest for the application of cooperative learning in teaching English. The result shows that the use of cooperative learning made the students interested in learning English. Keywords: Cooperative Learning, Reading Comprehension, Learning Method